2009
DOI: 10.1002/bio.1118
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dioxygen on luminol chemiluminescence

Abstract: Assays of peroxy compounds are commonly performed after chromatographic separation of analysed mixtures. In high-performance liquid chromatography (HPLC), solvent reservoirs are sparged by helium or inline vacuum-degassed in order to control the compressibility of the solvents for efficient pumping. In this study, we investigated the influence of degassing the reaction solution on the light output of the hemin-catalyzed luminol oxidation by various oxidants. We found that, when t-butyl hydroperoxide, hydrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Baj et al [97] discovered that partial exclusion of oxygen from the reaction medium strongly influenced the light intensity of the luminol reaction, and the effect is dependent on the oxidant analyzed, so an alternative mechanism was suggested for some oxidant species.…”
Section: Chemiluminescencementioning
confidence: 99%
“…Baj et al [97] discovered that partial exclusion of oxygen from the reaction medium strongly influenced the light intensity of the luminol reaction, and the effect is dependent on the oxidant analyzed, so an alternative mechanism was suggested for some oxidant species.…”
Section: Chemiluminescencementioning
confidence: 99%
“…Following Merényi and coworkers, 13,27,28 it is generally accepted [29][30][31] that the CL of luminol starts with electron transfer processes between redox couples. 32,33 By analogy with luminol, we assume that 1 is first dehydrogenated, allowing it then to add a nucleophilic hydroperoxide anion, and then to release a dinitrogen molecule leaving an excited phthalic acid derivative responsible for emitting a photon.…”
Section: Qualitative Experiments and Reaction Mechanismmentioning
confidence: 99%
“…Alternatively, more than one CL pathway can coexist in the same system. Baj et al (2009) reported that dioxygen could either quench or enhance luminol CL depending on the oxidant used (20). Quenching of CL emission was attributed to the blocking of the CL pathway involving O 2 /O 2 À while blocking of a less efficient CL pathway by certain oxidants caused an increase in CL emissions.…”
Section: Introductionmentioning
confidence: 99%